State-of-Art Functional Biomaterials for Tissue Engineering - Sharma, Krati; Mujawar, Mubarak A.; Kaushik, Ajeet (Frontiers in Materials, 2019)
Nanobiotechnology-enabled tissue engineering strategies have emerged as an innovative and promising technique in the field of regenerative medical science. The design and development of multifunctional smart biomaterials compatible to human physiology is crucial to achieve the required biological function with a reduced negative biological response. Several medical bioimplants have been tested to boost life expectancy and better-quality life. The concept of biocompatibility focuses on body acceptance and no harmful effects after implantation, which require shaping the properties of materials synthesis, surface functionalization, and biofunctionality. Such developed bioactive and biodegradable materials have been utilized to achieve the required function at a specific period and sustainability to withstand the surrounding tissues for treating severe injuries and diseases. Thus, exploring new approaches to design multifunctional biocompatible advanced nanostructures to develop next-generation therapies for tissue engineering, this mini-review is an attempt to summarize the advancements in biofunctional smart materials. The review focuses on bio-mimic materials, biomaterials, self-assembly biomaterials, bioprinting functional hydrogels, new polymeric architectures, and hybrid synthetic–natural hydrogels in the field of tissue engineering and regenerative medicine (TERM). This mini-review will serve as a guideline to design future research where the selection of a smart multifunctional biomaterial is crucial to obtain best TERM performance.